How AI is transforming extension services for precision smallholder farming - Gakhar, Shalini; Singaraju, Niyati (CGIAR Initiative on Digital Innovation, 2024)
Agriculture is at a transformative crossroads, where cutting-edge technology intersects with traditional farming practices. Artificial intelligence (AI) is emerging as a game-changer, enabling smarter, more efficient, and sustainable farming systems. By integrating real-time data from sources such as IoT sensors, drones, and advanced computer vision technologies, AI empowers farmers to make informed decisions tailored to the specific needs of their crops and environment (FAO, 2024). This precision-driven approach is not merely a technological leap but an essential response to the twin challenges of global food insecurity and climate change.